DAMPAK DAN UPAYA PENERAPAN IFRS PADA PELAPORAN KEUANGAN TERHADAP PERUSAHAAN DI INDONESIA - Agung Pratomo Sugito Putra, Toufiq; Tusholihah, Mardiyah; Retnawati, Kristianty; Ignasius Loyola Maje, Germanus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
The application of IFRS in several countries, Indonesia has also applies IFRS for financial reporting. After Indonesia implemented IFRS, there are several statements of Accounting Standards abolished or revoked. The conceptual changes of experienced by the accounting world in Indonesia, of course it will cause various impacts for the development of accounting science in Indonesia. The application of IFRS has a positive and negative impact on companies in Indonesia. This study using a qualitative descriptive approach, the type of research used literature study.  Data source in this study using secondary data. The results of research show that the industries companies can formulate  impact of these standards changes  together, so that they are more efficient. The standard which is principles based can be derived in the form of accounting guidelines for specific industries that can be used as references in preparing financial statements of companies in the industry.